Pemanfaatan Limbah Organik Rumah Tangga Sebagai Pupuk Cair di Kenagarian Halaban Jorong Atas Laban - Nurul Latifah; Ratna Willis; Audia Kasandra; Husnil Khotima; Adinda Adrianti; Shandy Melian Pajra; Adelia Kumala; Syah Alam Rahman Baharuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Household organic waste remains a significant environmental issue, particularly in rural areas where most residents rely on agriculture for their livelihoods. This community service program aimed to enhance community knowledge and skills in managing organic household waste through the production of eco-enzyme as liquid organic fertilizer. The program was conducted in Kenagarian Halaban, Jorong Atas Laban, Lima Puluh Kota Regency, involving 10 participants. The methods included community outreach, training sessions, hands-on practice, as well as continuous assistance and monitoring. Eco-enzyme was produced from household organic waste using a 3:1:10 ratio and fermented for 90 days, with 30 days of on-site assistance followed by online monitoring. The results showed that the eco-enzyme produced was dark brown in color with a distinctive acidic but non-putrid odor, indicating a successful fermentation process. The application of eco-enzyme as liquid fertilizer contributed to reducing organic waste volume, increasing environmental awareness, and improving plant growth. Limited community participation was identified as the main challenge, highlighting the need for broader engagement strategies to ensure program sustainability.